Promiscuity and preferences of metallothioneins: the cell rules - Foster, Andrew W (BioMed Central, 2011)
Metalloproteins are essential for many cellular functions, but it has not been clear how they distinguish between the different metals to bind the correct ones. A report in BMC Biology finds that preferences of two metallothionein isoforms for two different cations are due to inherent properties of these usually less discriminating proteins. Here these observations are discussed in the context of the cellular mechanisms that regulate metal binding to proteins. See research article: http://www.biomedcentral.com/1741-7007/9/4